Effect of REACT learning strategy on creative thinking and mathematical communication skills - Komarudin Komarudin; Mutia Mutia; Dini Palupi Putri; Ruhban Masykur; Suherman Suherman; Amelia Dwi Astuti (Universitas Nusantara PGRI Kediri, 2022)
This study aims to examine the effect of the REACT learning strategy on the creative thinking and mathematical communication skills of MTs/SMP students. The population of this research is class VIII MTs Ma'arif NU 5 academic year 2021/2022, totaling 122 students. The sample used is class VIII A as the experimental class using the REACT learning strategy and class VIII C as the control class. Hypothesis testing using Multivariate Analysis of Variance or MANOVA. The prerequisite test is the normality test with the Kolmogrov-Smirnov test and the homogeneity test against the Box's test and the Levianate test. The results of data analysis showed that the  so that  was rejected, the  then  was rejected, the  so  was rejected. Based on this analysis and calculation, it is concluded that there is an effect of REACT learning strategy on students' creative thinking skills, there is an effect of REACT learning strategy on students' mathematical communication skills. In addition, there is an effect of REACT learning strategy on students' creative thinking and mathematical communication skills.